ANALISIS PRAKIRAAN PRODUKSI DAN KONSUMSI BERAS INDONESIA - Andani, Apri (Jurnal AGRISEP, 2008)
The provisions of food in order to fullfil the humankind needs could be examined through the implementation of the process of agriculture production. However the requirement for food could only be fulfilled self-sufficiently if food supplies were higher than the total consumption. An increasingly descended trend of the increase of the Indonesian rice production was the problem that immediately must be overcome. This was caused by continously consumption growth resulting from the population growth. The aim of the research is to forecast the Indonesian Production and Rice Consumption, to estimate the supply capacity of domestic food (not including the import) compared with consumption of food nationally. To answer this aim, then it was carried out by the analysis of the forecast by using the method of Box-Jenkins with the model of ARIMA.The forecast result showed that the production of rice rise every year since the year of 2008-2012. The rise in general as big as 700 thousand ton per year is caused by the increase of the harvesting area as well as the land productivity. On the other hand, national rice consumption in aggregate also increased as big as 450 thousand ton every year. In 2012, consumption of the national rice is estimated tol reach more than 33 million ton. The continuing population growth results in increasing rice consumption per capita, but it shows a declined sign every year from 134 kg/capita in 2005 to only 130 kg/capita in 2012.  However, this result doesnot give any impact anything on total consumption.